Analisis Kinematik Power Clean Terhadap Klub Batavia Bersatu Maju 2024 - Michael Nicholas Purba; Iwan Hermawan; Boyke Adam Hatena Manopo (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2024)
The purpose of this study is to find out the kinematic analysis of power clean for the Batavia Bersatu Forward 2024 club. This type of research is research. The research population is several members of the Batavia Bersatu Maju weightlifting located in Parung Panjang, Jagabita village, Bogor Regency with a total of 16 lifters, 8 male members and 8 female members. The sampling technique uses Total Sampling as saturated sampling or census, is a sampling technique in which the entire research population is selected as a sample. Kinematic data collection of power clean, namely angles using APECS software media: Body Posture Evaluation by sampling, namely by recording a video after that and then analyzing each angle of kinematic movement of power clean. From the results of the kinematic analysis of the power clean, they include Hip Angle, Torso Angle and Knee Angle. The results of the study showed that athletes 1 to 16 were inferred to be the Angle that was present to analyze the power clean, namely the Knee Angle, Hip Angle, and Torso Angle. The number of Mean Knees was 114.1875 ago, the Mean Torso was 102.125 ago, and the Mean Hip was 131.354. Then the Median Knee Number 102, then the Median Torso 111, then the Median Hip Number 102, then finally the number of Knee Mode 111, then Torso Mode 104, then Hip Mode 128.5.